A novel functional screening assay to monitor sweet taste receptor activation in vitro. (21st November 2017) - Bastiaan‐Net, Shanna; van den Berg‐Somhorst, Dianne B.P.M.; Ariëns, Renata M.C.; Paques, Marcel; Mes, Jurriaan J.
Abstract: The human sweet taste receptor is a heterodimer comprised of the class C G protein‐coupled receptor (GPCR) subunits TAS1R2 and TAS1R3. A wide collection of sweet tasting compounds and modulators of sweet taste interact with this receptor. Although TAS1R2/TAS1R3‐mediated signaling is well‐studied, the molecular basis for its desensitization remains unclear while such knowledge would signify a profound step forward in understanding the mechanism behind sweet taste perception and taste modulation. In this work, the possible involvement of β‐arrestin in downstream signaling was investigated. A stable clonal Human Embryonic Kidney (HEK)‐derived cell line containing the PathHunter™ GPCR technology was developed, in which β‐arrestin‐mediated endosomal receptor internalization can be monitored by ligand‐induced enzyme complementation of β‐galactosidase (β‐gal). Stimulatory responses and antibody‐specific receptor detection indicated that the TAS1R2/TAS1R3 receptor is endogenously expressed in this clonal cell line. Natural sugars (including fructose, glucose, sucrose, maltose, maltitol and mannitol) and artificial sweeteners (acesulfame‐K and sucralose) stimulated enzyme complementation activity in a concentration dependent manner. Besides, we observed that the assay detected modification of sugar induced cell responses by sweetness enhancers. These results combined implicate that TAS1R2/TAS1R3 receptor desensitization by internalization is most likely mediated by β‐arrestin‐induced endocytosis. This assay approach, making use of naturally expressed TAS1R2/TAS1R3 receptors and required co‐factors, further allows effective screening for and development of novel high potency non‐caloric sweeteners, sweet taste modulators or optimal blends with enhanced sweet taste. Abstract : Sweet taste perception is mediated by the TAS1R2/TAS1R3 receptor. Using the PathHunter™ internalization assay, we found that β‐arrestin mediated endocytosis was necessary for receptor internalization and that a range of natural sugars, artificial sweeteners and sweet taste modulators induced receptor internalization in a concentration dependent manner.